Amy's language dilemma - Manyiri, Ron ([Publisher not identified], 2025)
"An inspirational story of a girl born to immigrant parents, who struggled with delayed speech due to exposure to multiple languages. Through resilience and determination, she excelled academically, pursued multiple degrees, and became fluent in five language, ultimately holding a top position at the United Nations headquarters."-- Back cover.